Wednesday

September 17, 2014

September 17, 2014

Posted by **Megan** on Wednesday, December 20, 2006 at 10:33pm.

I'm rather new at this but wouldn't b=2*sqrt(3) give (x+sqrt3)

Check my thinking.

for a quadratic equation to have exactly one root, the discriminat must be zero i.e

if equation is:

ax^2+bx+c=0 , then for exactly one root,

b^2-4ac=0

i.e.

b^2=4ac

for your equation,

x^2+bx+3=0

b^2=4(1)(3)

=12

hence

b=sqrt(12)

=2(sqrt(3))

**Answer this Question**

**Related Questions**

Derivatives - What is the fourth derivative of f(x)= e^-x^2. I got f''(x)=-2e^-x...

find dy/ds - y = s*square root of(1-s^2) + cos inverse(s) Just give me some ...

Algebra - Solve the quadratic equation. 4x^2-8x+3=5 4x² - 8x +3 - 5 = 0 4x²- 8x...

Powers in Math - (5a^3b^4)^2=? *I don't get this one...PLease Help! (5a3b4)2= (5...

Math - Simplify: 4^(-1/2) 4-1/2 = 1/41/2 = 1/2. check my work. On exponents, ...

Chemistry - Sorry for posting this again, I dont know if the question was ...

Property of logarithms - Using property of logarithms, how do I prove derivative...

Inter. Algebra - Count Iblis what is the answer to 2 square root sign 18x? The ...

Math - Hi i was wondering what the square root of 3 times the squareroot of 9 is...

Math - Is this correct: sqrt2/sqrt10=sqrt2/5sqrt2 nope. it would be sqrt2/(sqrt5...